2019
DOI: 10.1093/zoolinnean/zlz049
|View full text |Cite
|
Sign up to set email alerts
|

Assessing species boundaries in the open sea: an integrative taxonomic approach to the pteropod genus Diacavolinia

Abstract: To track changes in pelagic biodiversity in response to climate change, it is essential to accurately define species boundaries. Shelled pteropods are a group of holoplanktonic gastropods that have been proposed as bio-indicators because of their vulnerability to ocean acidification. A particularly suitable, yet challenging group for integrative taxonomy is the pteropod genus Diacavolinia, which has a circumglobal distribution and is the most species-rich pteropod genus, with 24 described species. We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…These authors found at least 10 additional atlantid clades that may represent new species in addition to the 23 currently described present-day species. This study, as well as many others (Goetze 2010; Burridge et al 2015, 2019; Barco et al 2016; Bode et al 2017; Cornils et al 2017), highlights the importance of combining morphology (morphometrics), biogeography and molecular analyses when exploring species diversity in the open ocean.…”
Section: Introductionsupporting
confidence: 52%
“…These authors found at least 10 additional atlantid clades that may represent new species in addition to the 23 currently described present-day species. This study, as well as many others (Goetze 2010; Burridge et al 2015, 2019; Barco et al 2016; Bode et al 2017; Cornils et al 2017), highlights the importance of combining morphology (morphometrics), biogeography and molecular analyses when exploring species diversity in the open ocean.…”
Section: Introductionsupporting
confidence: 52%
“…Shell shape variation has also been shown to have a large genetic component, with heritabilities ranging between 0.36 and 0.71 in L. saxatilis (Conde-Padín et al, 2007) and between 0.16 and 0.56 in Nucella lapillus (Guerra-Varela et al, 2009). Furthermore, shell shape differences in conjunction with genetic differentiation have been used to identify species boundaries in different genera of holoplanktonic gastropods (Burridge et al, 2015(Burridge et al, , 2019Wall-Palmer et al, 2018) using an integrative species concept (McManus & Katz, 2009;Padial et al, 2010). Hence, strong reproductive isolation is probably involved in the maintenance of this primary dispersal barrier in the southern Atlantic gyre.…”
Section: Discussionmentioning
confidence: 99%
“…Shelled pteropods are especially vulnerable to global change, because of their thin aragonitic shells that are prone to dissolution (Bednaršek, Tarling, et al., 2012; Lischka et al., 2011; Manno et al., 2017), and they have been suggested as bioindicators of the effects of ocean acidification (Bednaršek, Klinger, et al., 2017). Several prior genetic studies on shelled pteropods have focused on resolving species boundaries via an integrative approach, combining genetic analyses and morphometric measurements of shells, to obtain a better understanding of species distribution patterns (Burridge et al., 2015, 2019; Shimizu et al., 2018). Other recent research efforts have addressed the response of shelled pteropods to acidified conditions to evaluate their acclimation to rapid increases in ocean acidity (Bednaršek, Feely, et al., 2017; Bogan et al., 2020; Maas et al., 2018; Moya et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These groups should be a priority for future DNA barcoding efforts, although challenges include lack of specimen vouchers due to poor preservation in ethanol. Recent studies have demonstrated the power of integrated molecular and morphometric analyses for these groups (Burridge et al 2015(Burridge et al , 2019Shimizu et al 2018;Choo et al 2020). Discovery of new species and increased estimates of global diversity can be expected, especially for species with widespread and multi-ocean distributions, which may be expected to reveal evidence of cryptic speciation.…”
Section: Gastropodamentioning
confidence: 99%